“Bush Law 101”: Realising Place Conscious Pedagogy in the Law Curriculum - Kennedy, Amanda; Mundy, Trish; Nielsen, Jennifer (Journal of University Teaching and Learning Practice, 2016)
In 2012, a team of academics from six universities worked on an OLT-funded project, ‘Rethinking Law Curriculum: developing strategies to prepare law graduates for practice in rural and regional Australia’. The project was motivated by the declining proportion of lawyers being attracted to and remaining in practice in rural and regional Australia. The main outcome of the project was an open education resource designed to sensitise students to the realities of the rural and regional legal practice context in the form of a customisable curriculum package that can be embedded as components within existing units of study, or developed as a stand-alone unit.Three of the team members have now implemented the curriculum package within their law school programs, two in the form of a stand-alone elective unit delivered to undergraduate law students, and the third to support placement programs for law and paralegal students. Applying the process of peer observation and collaborative reflection, this paper reports on their experiences to offer insights on how to adapt and integrate the ‘Rethinking law’ package within the law school curriculum. In particular, this paper will discuss the significance of place-consciousness as a pedagogical tool, and the capacity of the ‘Rethinking Law’ package to encourage law students to ‘re-imagine’ careers in rural and regional Australia and their role as the country’s future lawyers.